Lexic-Grammatical Markers of the Manipulativeness of Mass Media Discourse (based on the Material of the Body of Russian-Language Media Texts in Republic of Kazakhstan) - M. T. Shakenova; D. S. Tashimkhanova; U. A. Ospanova; T. K. Buldybayev (Научный диалог)
The article is devoted to the phenomenon of manipulative mass media discourse. The results of the analysis of Kazakhstani media with verbally expressed manipulative discursive practice are presented. The research material was the Russian-language texts of opposition newspapers and information and analytical portals of the Republic of Kazakhstan. The choice of the source of factual material is due to the fact that it is in such a mass media discourse that language markers of the manipulability of the text are most pronounced. Given the generalization of the results of modern research, the concept of the manipulative nature of mass media discourse is defined. As a result of the analysis of texts from the position of cognitive-discursive and linguistic approaches, the main lexical, morphological and syntactic markers of manipulativeness are identified. For the first time, syntactic tools are described and formalized in which predicates in collocation with lexical and morphological tools form lexical and grammatical markers - statistically valid indicators of computer diagnostics of manipulativeness as a factor of a certain information threat to society. The results of the study can be theoretically and practically significant in the fields of sociology, political science, pragmatic linguistics, journalism, and information technology.